New gladiolus variety Pusa Sinduri - Swaroop, Kishan; Janakiram, T; Singh, Kanwar Pal; Kumar, Prabhat; Sindhu, S S; Dhiman, M R (Indian Horticulture, 2018)
Gladiolus Pusa Sinduri is a new variety developed by scientists of IARI, New Delhi. It is ideal for cut flower, bouquet, vase and floral arrangements. Its multicoloured florets are highly attractive. They make it ideal for all occasions.